All-optical field-free three-dimensional orientation of asymmetric-top molecules. Issue 1 (December 2018) - Lin, Kang; Tutunnikov, Ilia; Qiang, Junjie; Ma, Junyang; Song, Qiying; Ji, Qinying; Zhang, Wenbin; Li, Hanxiao; Sun, Fenghao; Gong, Xiaochun; Li, Hui; Lu, Peifen; et al.
Abstract Orientation and alignment of molecules by ultrashort laser pulses is crucial for a variety of applications and has long been of interest in physics and chemistry, with the special emphasis on stereodynamics in chemical reactions and molecular orbitals imaging. As compared to the laser-induced molecular alignment, which has been extensively studied and demonstrated, achieving molecular orientation is a much more challenging task, especially in the case of asymmetric-top molecules. Here, we report the experimental demonstration of all-optical field-free three-dimensional orientation of asymmetric-top molecules by means of phase-locked cross-polarized two-color laser pulse. This approach is based on nonlinear optical mixing process caused by the off-diagonal elements of the molecular hyperpolarizability tensor. It is demonstrated on SO2 molecules and is applicable to a variety of complex nonlinear molecules. Alignment and orientation of the molecules allows studying the photon-molecule interactions in greater detail. Here the authors demonstrate the three-dimensional orientation of SO2 molecules in using COLTRIMS and orthogonally polarized laser pulses but in the absence of DC field.